The observance of human right to freedom from torture in professional activity of the National Police of Ukraine (article 3 of the Convention for the protection of human rights and fundamental freedoms) - Войціховський, А. В.; Voitsikhovskyi, A. V.; Bakumov, O. S.; Бакумов, О. С.; Ustymenko, O. S.; Устименко, О. С.; Seliukov, V. S.; Селюков, В. С.; Андрій Войціховський (JANUS.NET: e-journal of International Relations. - 2019. - Vol. 10, N.º 2. - P. 152-165, 2019)
У статті розглядається питання дотримання органами Національної поліції України права людини на свободу від катувань чи нелюдського поводження або покарання. Практика Європейського суду з прав людини свідчить про те, що українці все частіше звертаються до суду за порушеннями заборони на катування або нелюдське поводження з боку поліції. Дотримання національного законодавства, застосування положень Конвенції про захист прав людини і основоположних свобод та практика Європейського суду з прав людини будуть сприяти підвищенню суспільної довіри і поваги до правоохоронних органів і підвищенню ефективності української судової системи.

The article considers the issue of observance by the bodies of the National Police of Ukraine of human right to freedom from torture or inhuman treatment or punishment. The practice of the European Court of Human Rights testifies that Ukrainians are increasingly applying to the Court for violations of the prohibition of torture or inhuman treatment by the police. The authors noted that the responsibility of the bodies of the National Police of Ukraine to prevent violations of human rights to freedom from torture or inhuman treatment was enshrined both in national law and in international legal documents, especially in the Convention for the Protection of Human Rights and Fundamental Freedoms of 1950. The application of the provisions of the Convention, as well as the decisions of the European Court of Human Rights as an integral part of its law enforcement practice, will contribute to the development of the protection of human rights in Ukraine. Summarizing the practice of the European Court of Human Rights in relation to Ukraine regarding violations of Article 3 of the Convention, the authors of the research singled out certain requirements that are binding on the bodies of the National Police of Ukraine. The observance of national legislation, application of the provisions of the Convention for the Protection of Human Rights and Fundamental Freedoms and the practice of the European Court of Human Rights will contribute the increasing of the public trust and respect for the law enforcement agencies, including the National Police of Ukraine and improving the efficiency of the Ukrainian justice system.

В статье рассматривается вопрос соблюдения органами Национальной полиции Украины права человека на свободу от пыток или бесчеловечного обращения или наказания. Практика Европейского суда по правам человека свидетельствует о том, что украинцы все чаще обращаются в суд за нарушениями запрета на пытки или бесчеловечное обращение со стороны полиции. Соблюдение национального законодательства, применение положений Конвенции о защите прав человека и основных свобод и практика Европейского суда по правам человека будут способствовать повышению общественного доверия и уважения к правоохранительным органам и повышению эффективности украинской судебной системы.
Keywords: Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; publikatsii u zarubizhnomu vydanni; publikatsii u Scopus; torture or inhuman treatment, or punishment; European Court of Human Rights; Convention for the Protection of Human Rights and Fundamental Freedoms; National police of Ukraine; Національна поліція України. National police of Ukraine. Национальная полиция Украины; Национальная полиция Украины; катування або нелюдське поводження, або покарання; Європейський суд з прав людини; Конвенція захисту прав людини та основних свобод; Міжнародне право .International Law. Международное право; пытки или бесчеловечное обращение или наказание; Европейский суд по правам человека; Конвенция по защите прав человека и основных свобод